Analysis of Health Services for People with Mental Disorders (ODGJ) at the Kampar District Health Office in 2021 - Andriani, Rini; Harnani, Yessi; Afridayanti, Afridayanti (Universitas Muhammadiyah Kalimantan Timur, 2022)
Background : According to the Law of the Republic of Indonesia No.18 of 2014 Mental Health is a condition that allows an individual to develop physically, mentally, spiritually, and socially so that the individual is aware of his own abilities, can cope with pressure, can work productively and is able to contribute to their community (Ministry of Health, 2014). Data from the Kampar District Health Office in 2019 there was an increase in cases of People With Mental Disorders (ODGJ) in 2020 totaling 141 people with a prevalence of 0.15 of the population. In 2020, it has a target of 1,218 people, only 781 people recorded and 535 people received health services. The highest cases of mental disorders were in the working area of ​​the Mining Community Health Center with 121 cases. The Community Health Center with the lowest cases of mental disorders was Kampar Kiri Hulu II Health Center with 5 cases of mental disorders. Objective : To identify the problems found and provide recommendations for alternative solutions regarding the Health Services for People with Mental Disorders (ODGJ) at the Kampar District Health Office. Method : qualitative using fishbone Data collection was carried out by means of observation, interviews and document searches at the Kampar District Health Office. Results: Based on the analysis, it was found that health services for people with severe mental disorders (ODGJ) and non-communicable diseases (hypertension and diabetes mellitus) were found in Kampar Regency. The priority problem through ultrasound weighting is the lack of health services for people with severe mental disorders (ODGJ). Conclusion: The problem solving recommendations given are asking for cross-sectoral support to increase awareness of mental health, proposing/producing more posters, books, leaflets related to mental health, conducting training on early detection of mental disorders for officers from community health centers.